The golden alloy Cu-5Zn-5Al-1Sn: A multi-analytical surface characterization. (February 2018) - Chang, Tingru; Wallinder, Inger Odnevall; Jin, Ying; Leygraf, Christofer
Highlights: Cu5Zn5Al1Sn possesses a fine microstructure and a homogeneous surface chemical composition. A 5–10 nm thick oxide rapidly forms after diamond polishing. The oxide consists of 88 mass% of Cu2 O, 8 mass% of ZnO, 4 mass% of SnO2, besides an unknown mass proportion of Al2 O3 . The four identified sub-oxides all contribute to the overall corrosion resistance. Abstract: The golden alloy Cu-5Zn-5Al-1Sn has found many applications because of its appearance and resistance to tarnishing. The microstructure and multi-component surface oxide of Cu-5Zn-5Al-1Sn have been investigated through a multi-analytical approach. Compared to commercial Cu metal, Cu-5Zn-5Al-1Sn has significantly smaller grains and higher fraction of coherent twin boundaries. The 5–10 nm thick oxide formed after diamond polishing has four identified sub-oxides all contributing to the overall corrosion resistance. Cu2 O is mainly located in the outer part, followed by ZnO, SnO2 and Al2 O3 closer to the alloy substrate. The latter three possess barrier properties, while Cu2 O exhibits a more complex structure.